HAK AZASI MANUSIA PERSPEKTIF SYARIAH MENURUT ABDULLAH AHMAD AL-NA’IM - Munir, Munir (Nurani, 2013)
Abstract: Anthropologically, human's life in the fields of economy, education, culture, politics and behavior is mostly affected by his basic and principal world-view that is believed as high valued truth. Meanwhile, that view is mainly formed by his belief of some values with profane and transcendental dimension. Transcendental values are mostly formed by religious belief. In plural society's life sometimes there are some clashes between world-view and social reality, particularly when they are related with the context of current globalization life. This article discusses hamisasi syari'ah, a study of Abdullah Ahmad al-Naim's thought.ملخص: أنثروبولوجيا، وتتأثر حياة الإنسان في مجالات الاقتصاد والتعليم والثقافة والسياسة والسلوك في الغالب من قبل صاحب الأساسي والرئيسي للعالم التي يعتقد أنها الحقيقة وقيمتها عالية. في هذه الأثناء، يتم تشكيل هذا الرأي أساسا من اعتقاده بعض القيم مع البعد تدنيس والمتسامي. تتشكل القيم المتعالية في الغالب من قبل المعتقدات الدينية. في حياة المجتمع التعددي في بعض الأحيان هناك بعض الاشتباكات بين النظرة إلى العالم والواقع الاجتماعي، وخاصة عندما ترتبط أنها مع السياق الحالي للعولمة الحياة. تتناول هذه المقالة الشريعة حقوق الإنسان، دراسة الفكر عبد الله أحمد النعيم لل.Kata kunci:  hak asasi manusia, syari'ah